ANALISIS EFEKTIFITAS PROGRAM BANTUAN KEUANGAN KHUSUS (BKK) GERBANGSADU MANDARA DI KABUPATEN KARANGASEM TAHUN 2017 (STUDI KASUS PADA 18 DESA KAWASAN RAWAN BENCANA ERUPSI GUNUNG AGUNG) - Komang Agus Rudi Indra Laksmana; I Ketut Merta (Master of Management, Mataram University, 2020)
Karangasem Regency is one of the regencies in Bali which has the highest poverty rate in Bali, The Gerbangsadu Mandara program in 2016 has been distributed in 54 villages with an average budget of 1 billion rupiah per village. However, in mid 2017 the eruption of Mount Agung erupted causing economic paralysis in 22 affected villages in Karangasem Regency. Among them 18 villages are disaster prone areas (KRB) are recipients of the Gerbangsadu Mandara program. Indicators in measuring effectiveness used are performance measurement instruments for 2016-2018 in the form of CCR, ROI, LAR financial ratios aimed at measuring health and its relation to the readiness of citizens to receive further intervention from the government for the following year. The problems to be solved in this study are: How is the effectiveness of Gerbangsadu Mandara Special Financial Assistance (BKK) in 18 villages of Mount Agung Eruption in Karangasem Regency as seen from Cost Coverage Ratio (CCr), Return on Investment (ROI), and Loan at Risk (LAR). The results showed that during the period 2016-2018, the average performance of 18 Bumdes in Karangasem Regency for a Cost Coverage Ratio (CCr) ratio of 183% (very satisfying), Return on Investment (ROI) of 7% (quite satisfactory), and Loan at Risk (LAR) of 19% (minimum). Paired T-test shows that Sign.2-tailed value is greater than 0.05, it means that financial performance before and after the eruption of Mount Agung did not occur a significant significant difference. The conclusion is that the Bumdes financial performance in Karangasem Regency is not affected by the risk of the eruption of Mount Agung. The limitation of the research lies in the object of research at one financial institution that is Bumdes, further research this concept can be tested at other financial institutions such as Village Credit Institutions, Banks and Cooperatives.